'A Clear and Honest Understanding': Alan Fox and the Origins and Implications of Radical Pluralism. Issue 38 (September 2017) - Gold, Michael
Abstract : One of the most significant contributions to industrial relations theory over the last forty years has been Alan Fox's elaboration of 'radical pluralism' as an analytical frame of reference. Though still highly influential, it has recently been criticized by Peter Ackers for allegedly confusing sociological and historical methodological procedures, prioritizing conflict over co-operation at the workplace, and lacking connection with policy-makers. This article, through close reference to Durkheim, demonstrates how and where radical pluralism differs from Marxist analysis, and why the distinction is so important in answering these criticisms. It concludes that radical pluralism, with its nuanced understanding of the complexities of social inequalities, has potentially a great deal to offer both analysts of contemporary industrial relations and policy-makers.